Agentic Engagement Siswa: Tinjauan Literatur Sistematik - Muhammad Faiz Makarim; Linda Primana (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2023)
Engagement is the effort that students make by directly contributing to achieving the goal of learning success. Student engagement is considered a predictor of improved learning performance, academic achievement and socializing quality of learners. Research on engagement in educational contexts has grown in recent years. The concept of engagement that is often used in recent research is student engagement with three aspects, namely, behavior, emotional, and cognitive engagement. Then there are studies that suggest that the theory of engagement so far only sees student behavior as a passive recipient of information from the teacher. Therefore, the concept of engagement is developed by adding one construct, namely, agentic engagement. This construct explains engagement as proactive behavior that arises from students' initiatives that are constructive for the learning environment. This article aims to review: (a) the concept of agentic engagement in current research and (b) factors that influence agentic engagement in the learning context. The method used is a systematic literature review. The results of this review indicate that the construct of agentic engagement is a recent component of student engagement. The conclusions of this systematic literature review are, (a) agentic engagement is an important predictor of learning success, (b) agentic engagement can be influenced by internal and external factors, and (c) the role of teachers in providing autonomy support to students is important to encourage students' motivation to be agentically engaged in learning. The findings of this systematic literature review can be followed up by teachers, schools and parents to design lessons that support students' agentic engagement.